A Role for the DOF Transcription Factor BPBF in the Regulation of Gibberellin-Responsive Genes in Barley Aleurone - Mena, Montaña (American Society of Plant Physiologists, 2002)
Functional analyses of a number of hydrolase gene promoters, induced by gibberellin (GA) in aleurone cells following germination, have identified a GA-responsive complex as a tripartite element containing a pyrimidine box motif 5′-CCTTTT-3′. We describe here that BPBF, a barley (Hordeum vulgare) transcription factor of the DOF (DNA-Binding with One Finger) class, previously shown to be an activator of reserve protein encoding genes during development, also has a role in the control of hydrolase genes following seed germination. Northern-blot, reverse transcriptase-polymerase chain reaction, and in situ hybridization analyses evidenced that the transcripts of the BPBF-encoding gene (Pbf), besides being present during endosperm development, are also expressed in aleurone cells of germinated seeds where they are induced by GA, an effect counteracted by abscisic acid. Electrophoretic mobility shift assays have shown that the BPBF protein binds specifically to the pyrimidine box motif in vitro within the different sequence contexts that naturally occur in the promoters of genes encoding a cathepsin B-like protease (Al21) and a low-isoelectric point α-amylase (Amy2/32b), both induced in the aleurone layers in response to GA. In transient expression experiments, BPBF repressed transcription of the Al21 promoter in GA-treated barley aleurone layers and reverted the GAMYB-mediated activation of this protease promoter.